Validation of the Cadre’s Satisfaction of the Posyandu Lansia Questionnaire - Shahla Trisa Aufa; Sharon Gondodiputro; Neneng Martini (Universitas Islam Bandung, 2022)
Integrated health post for elderly/posyandu lansia is one of the community empowerment actions in improving the quality of life of the elderly. The role of cadres in managing the posyandu lansia is significant and is influenced by motivational factors that will cause satisfaction or dissatisfaction at work. A qualitative study in Bandung succeeded in exploring the components of satisfaction based on Herzberg's theory. Until now, no questionnaires have been developed to measure the satisfaction of posyandu lansia cadres. This study aims to set up and validate the satisfaction questionnaire for posyandu lansia cadres. A cross-sectional study was conducted on 200 cadres taken by multistage sampling in Bandung, West Java, Indonesia, from October to November 2020. Fifty-four items consisting of 19 motivator factor items and 35 hygiene factor items were tested for validity using the Pearson product-moment correlation coefficient, exploratory factor analysis, and communalities test. In addition, a reliability test was carried out using Cronbach's alpha. The results showed that 16 of 54 items did not meet the requirements, consisting of 5 items from motivator factors and 11 from hygiene factors. The dimensions of the motivator factors changed from 6 dimensions to 4 dimensions, and the dimensions of hygiene factors changed from 8 dimensions to 9 dimensions. It concluded that a new questionnaire on the satisfaction of posyandu lansia cadres has been compiled and can be used to measure the level of satisfaction of cadres. However, further studies need to be carried out involving various regions in Indonesia.